«Հաճախապատում ճառք»-ի հնագույն ձեռագրերի և հրատարակությունների հարցի շուրջ - Նելլի Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
В данной статье мы обратились к вопросу о рукописях одного из важнейших произведений армянской церковной литературы, называемого «Многовещательные речи», и их публикациях. This article is a study of the different manuscripts and publications of "Faitful Speech", one of the Armenian Apostolic Church's most important works of literature.
Keywords: Bibliography; Manuscripts; Paleography